2009
DOI: 10.1645/ge-1103.1
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Human Myiasis in Goiás State, Brazil: Frequency of Different Types of Myiasis, Their Various Etiological Agents, and Associated Factors

Abstract: The objective of this study was to show which species of flies are responsible for human myiasis in the Brazilian state of Goiás and to determine the frequency of cases. Patients at the Clinical Hospital of the Federal University of Goiás (UFG) were examined, and any fly larvae found in their wounds were collected for taxonomic identification. First instar larvae were observed using light microscopy; second and third instars were examined using stereoscopy. The following screwworm flies were observed, in decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 9 publications
2
46
0
6
Order By: Relevance
“…Sarcodexia lambens showed a strong attraction for fish and chicken viscera, in accordance to other studies where this species has been found in a large proportion in corpses (Barros et al 2008). However, it is an opportunistic species and it has been attracted by a variety of substrata, such as pig and human corpses (Oliveira-Costa et al 2001, Barros et al 2008, Barbosa et al 2009, and even causing myasis in humans (Queiroz de Leão et al 1996, Fernandes et al 2009) and frogs (Hagman et al 2005). Linhares (1981) reported Helicobia morionella (Aldrich, 1930) attracted by chicken viscera, mouse corpses and human faeces, showed the highest abundance in the latter; it also resulted in a synanthropic index that reveals a complete rejection for human settlements.…”
Section: Discussionsupporting
confidence: 85%
“…Sarcodexia lambens showed a strong attraction for fish and chicken viscera, in accordance to other studies where this species has been found in a large proportion in corpses (Barros et al 2008). However, it is an opportunistic species and it has been attracted by a variety of substrata, such as pig and human corpses (Oliveira-Costa et al 2001, Barros et al 2008, Barbosa et al 2009, and even causing myasis in humans (Queiroz de Leão et al 1996, Fernandes et al 2009) and frogs (Hagman et al 2005). Linhares (1981) reported Helicobia morionella (Aldrich, 1930) attracted by chicken viscera, mouse corpses and human faeces, showed the highest abundance in the latter; it also resulted in a synanthropic index that reveals a complete rejection for human settlements.…”
Section: Discussionsupporting
confidence: 85%
“…Species causing myiasis can be classified into three parasitological categories: obligatory, facultative, and accidental. An obligatory parasite requires living tissue for the development of invaded larvae [10] . Clinically, species classification is based on the infested area of the host body that includes cutaneous, enteric, ophthalmic, nasopharyngeal, auricular, and urogenital [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Among these flies, D. hominis is the most common agent of both cutaneous myiasis and furuncular myiasis diagnosed in returning travelers [6][7][8][9] . This species is distributed through Mexico to Argentina of Central and South America, in areas of relatively high temperature and humidity [10] . Because D. hominis is not endemic in Taiwan and the caused lesion resembles a furuncle in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all cases are present on scalp, limbs and back although infestations of the eye, the breast and the genitalia have been observed. 3,7,[9][10][11][12][13][14][15][16][17][18][19] A case of an erysipelas-like lesion resulting from an unusual infestation with nine larvae of Dermatobia hominis was described. In this case local application of petroleum jelly allowed the exit all larvae.…”
Section: Discussionmentioning
confidence: 99%